Setting limits with your strong-willed child eaudiobook Eliminating conflict by establishing clear, firm, and respectful boundaries. - MacKenzie, Ed.D, Robert J. (Tantor Media, 2011)
Does your child constantly misbehave and ignore or refuse your requests? Is your relationship with your child based on conflict instead of mutual respect and cooperation? With the help of this groundbreaking book, you can create a positive, respectful, and rewarding relationship with your child. Setting Limits with Your Strong-Willed Child contains proven techniques and procedures that provide a refreshing alternative to the ineffective extremes of punishment and permissiveness. Parents and teachers alike will discover how to effectively motivate the strong-willed child and achieve cooperation. You will learn how to: Understand and empathize without giving in Hold your ground without threatening Remove daily power struggles between you and your child Give clear, firm messages that your child understands and respects And much more!